THE EMPIRICAL EXAMINATION OF VALUE CREATION CRITERIA: ACHIEVING CONSENSUS USING DELPHI EXERCISE WITHIN SERVICE INDUSTRY - Suzila, Mohamed Yusof; Amizawati, Mohd Amir; Norida, Basnan; Sofiah, Md. Auzair (UNIMAS Publisher, 2025)
Businesses recognise the strategic significance of customer participation in value creation in an increasingly competitive market environment. However, despite growing interest in customer engagement, there is still little empirical research on the precise contributions suggested by customer experts to value creation, despite the increased interest in customer interaction. This paper aims to provide recommendations on value creation criteria, covering both financial and non-financial dimensions, based on the consensus reached through a Delphi exercise involving customer experts with in-depth knowledge of services. The Delphi practice is a methodical approach to gathering expert opinions, aiming to achieve a definitive agreement among the designated experts. Nine experts were involved in the Delphi exercise until consensus or agreement was reached in the third cycle. The results reveal that the panel members reached consensus on many new issues pertaining to both financial and non-financial aspects. The results contribute to the growing body of studies on consumer participation in value creation and organisations’ potential to enhance their relationships with customer experts. This also contributes to SDG 8 (Economic Growth and Decent Work) in boosting productivity, innovation, and employment in the service industry.